PROSES IDENTIFIKASI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI MI NW TANAK BEAK KABUPATEN LOMBOK BARAT - Arif Widodo; Linda Feni Haryati; Mohammad Archi Maulyda; Umar Umar; Muhammad Erfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
The identification process is the first step in determining the special needs of the students. This process is important to be carried out as a basis for conducting assessments and developing individual learning programs for students with special needs. The method used in this research is descriptive qualitative. Data collection through in-depth observation, interviews, and documentation. The instruments used were observation and interview guidelines. Observations were made to observe the behavior of students both physically and non-physically when in the madrasa environment. Data is presented in the form of diagrams and then analyzed descriptively. Checking the validity of the findings is done by extending participation in the observation process. The results showed that 54 students were identified as having special needs. Specific types of needs found include impaired concentration and hyperactivity, specific learning difficulties, slow learning, visual impairment, visual impairment, hearing loss, and behavior and emotional disorders. Among these types of special needs are dominated by students with impaired concentration and hyperactivity with 39% of students with special needs.